Skill enhancement for post graduate medical students - K., Narayanasamy; S., Pushkala (International Journal of Research in Medical Sciences, 2025)
The medical students ought to be well versed with life saving measures like basic and advanced techniques and should also practice medicine in the most ethical manner in today’s healthcare environment. To provide a uniform formal training to all the post graduate medical students it was decided to start the BLS/ALS/GLP/GCP courses across the state using uniform modules developed by experts. To implement this uniformly, The Tamil Nadu Dr. M. G. R. medical university initiated training programs in advanced life support (ALS), basic life support (BLS), and good clinical practice (GCP), good laboratory practice (GLP) through eight designated nodal centres across Tamil Nadu. A total of 4,000 postgraduate medical students received training from qualified personnel. Pre and post training assessments were conducted to evaluate the effectiveness of the program. The feedback collected from students was highly encouraging, indicating a positive reception of the training modules, and reaffirming the program’s value and effectiveness.